Определение границы устойчивости лопаточных венцов к дозвуковому флаттеру при больших углах атаки - Кабанник, С.Н.; Зиньковский, А.П.; Стельмах, А.Л. (Проблемы прочности, 2018)
This paper presents an experimental-numerical method for determination of the subsonic flutter stability boundary of blade rows at large angles of incident flow. The aerodynamic test rig for determining the unsteady aerodynamic loads is described. The test results are presented for a straight cascade of airfoils in a wide range of variation in the angle of attack and reduced vibration frequency, based on which the regularities in the effect of the angle of attack on the subsonic flutter stability boundary of blading are established.